Socio-Economic Impacts of Agricultural Production in North East India: A Comprehensive Review - Dr. Tongkholal Baite (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Agriculture plays a central role in sustaining rural livelihoods, household income, foodsecurity and socio-economic development in North East India, yet its potential remainsconstrained by fragmented landholdings, difficult terrain, inadequate irrigation and mechanisation, weak market infrastructure, limited institutional support